Taylor's differential diagnosis manual : symptoms and signs in the time-limited encounter - Paulman, Paul M., 1953-; Taylor, Robert B.; ebrary, Inc. (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2014)
"Taylor's Differential Diagnosis manual is a quick-reference pocket book, written for primary care professionals who face diagnostic problems in brief office visits. It offers evidence-based guidelines on which key questions to ask and what data to obtain in order to provide sound diagnoses of common adult problems. More than 140 chapters in eighteen sections cover symptoms and signs in mental health problems, vision, ear nose and throat, cardiovascular, respiratory, urologic, female reproductive, musculoskeletal, dermatology and more. New for this edition are new chapters on abnormal mammogram, anticoagulation, bipolar disorder, corneal abrasion, dyspareunia and loss of vision as well as the latest clinical evidence and changes in clinical practice since the prior edition"--Provided by publisher.
Rev. edition of: Taylor's 10-minute diagnosis manual. 2nd edition c2007.
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Palo Alto, Calif. : ebrary, 2014. Available via World Wide Web. Access may be limited to ebrary affiliated libraries.
Keywords: Symptoms -- Handbooks, manuals, etc; Electronic books